المؤلّفُ ومفسروه - تبرماسين, عبد الرحمان; الوافي, سامي (قــــــراءات; No 08 (2015): (مجلة قراءات( مارس, 2019)
يوجد في القراءة النقدية تعاملٌ يضعُ النص الإبداعي في مهب الجماليات البالغة التنوع لدى القارئ النموذجي المفترض، لتجسّدهِ ككائنٍ متذوقٍ بامتياز، لأنه يرشح نفسه لاكتشافه من شرفة تجربته الخاصة. Abstract :     the critical reading of the creative text places it in the framework of the very diverse aesthetics for the ideal supposed reader ; as he  is considered  as an excellent taster because he nominates himself to discover it from the balcony of his own experience .